2005
DOI: 10.1210/jc.2005-0780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physiological Leptin Administration on Markers of Inflammation, Platelet Activation, and Platelet Aggregation during Caloric Deprivation

Abstract: Our data provide evidence that physiological leptin administration stimulates inflammatory and platelet responses in humans during caloric deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 28 publications
2
57
0
3
Order By: Relevance
“…Leptin-induced platelet aggregation is blunted, but not completely abolished, in overweight and obese patients when compared to normal weight subjects, and this observation suggests that leptin receptor on platelet membrane may represent a site of leptin resistance in human obesity. 19 These findings have been recently extended by Canavan et al 39 by demonstrating that normal weight subjects undergoing complete caloric deprivation had greater sensitivity in hemostatic responses to leptin. The present study further confirms the existence of a differential sensitivity to the pro-thrombotic action of leptin effect based on total adiposity, and suggests the hypothesis that platelet resistance to leptin in overweight or obese patients could represent a finalistic protective mechanism against the excess pro-thrombotic stimulation that would be produced by obesity-related hyperleptinemia.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Leptin-induced platelet aggregation is blunted, but not completely abolished, in overweight and obese patients when compared to normal weight subjects, and this observation suggests that leptin receptor on platelet membrane may represent a site of leptin resistance in human obesity. 19 These findings have been recently extended by Canavan et al 39 by demonstrating that normal weight subjects undergoing complete caloric deprivation had greater sensitivity in hemostatic responses to leptin. The present study further confirms the existence of a differential sensitivity to the pro-thrombotic action of leptin effect based on total adiposity, and suggests the hypothesis that platelet resistance to leptin in overweight or obese patients could represent a finalistic protective mechanism against the excess pro-thrombotic stimulation that would be produced by obesity-related hyperleptinemia.…”
Section: Discussionmentioning
confidence: 64%
“…Finally, the cross-sectional design does not allow us to verify whether leptin-dependent platelet aggregation increases with weight loss, improvement of leptin sensitivity and reduced leptin levels. Although in normal weight subjects caloric deprivation produce a greater hemostatic Metabolic syndrome and platelet response to leptin F Corica et al responses to leptin, 39 this finding need to be prospectively replicated in overweight and obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously performed interventional studies in normo-or hyperleptinaemic lean and obese men and women, demonstrating that increasing leptin levels, through leptin administration, did not result in any significant change in several inflammatory markers associated with CVD in both short-term (3 days) and longer-term (16 weeks) studies [11]. In contrast, in human studies involving leptin administration in low leptin states, including congenital leptin deficiency and starvationinduced hypoleptinaemia, leptin administration was associated with a significant increase in inflammatory markers and increased platelet aggregation [3,10]. On the basis of the differing biological activity of leptin in low vs high leptin states the association with inflammatory biomarkers in obesity, a hyperleptinaemic leptin-resistant state, does not appear to be causal.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although interventional studies in humans have shown that leptin administration in low leptin states is associated with increased inflammatory and platelet responses [3,10], there appears to be no significant effect of leptin administration in leptin-replete states such as obesity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin levels are correlated with circulating levels of CRP, 30 and exogenous leptin increases CRP levels in normal-weight subjects but not in obese subjects, 31 and CRP decreases markedly during fasting-induced hypoleptinaemia. 32 The known direct proatherogenic effects of CRP 33 may thus be partly regulated by leptin. Leptin interacts with lipid metabolism at several levels: by stimulating macrophages to secrete lipoprotein lipase in the vessel wall; 34 by increasing the accumulation of cholesterol esters in foam cells, especially during hyperglycaemia 6 and by lowering HDL through increased clearance consequent on the upregulation of the scavenger receptor.…”
Section: 23mentioning
confidence: 99%